2002
DOI: 10.1002/qua.987
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical ab initio study of ranitidine

Abstract: ABSTRACT:The presence of a heterocyclic ring containing a basic center linked via a methylene chain to a substituted guanidine or thiourea polar side chain, such as found in the H2-antagonist metiamide, which has an imidazole heterocyclic ring, has often been identified as one of the requirements for H2-antagonist activity. In ranitidine, on the other hand, the imidazole ring is substituted for a furan ring, yielding a more active biological H2 antagonist. In this work, we have used the ab initio Hartree-Fock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…24 -29 . Ranitidine hydrochloride has been investigated in relation to crystallographic data, 30 but the authors are unaware of any other studies involving drug polymorphism and prediction of the vibrational spectra of drug polymorphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 -29 . Ranitidine hydrochloride has been investigated in relation to crystallographic data, 30 but the authors are unaware of any other studies involving drug polymorphism and prediction of the vibrational spectra of drug polymorphs.…”
Section: Introductionmentioning
confidence: 99%
“…This may be contrasted with the flexible structure of other drugs, such as ranitidine, where the polymorphs are structurally more different. Martins et al, 30 in a comprehensive study of the different forms of ranitidine (folded versus open structure), demonstrated that the prediction of H-bonded species was sensitive to basis set and method; however, many of the other structural properties, bond lengths and angles were much less dependent on the level of basis set or methods used. The structure of carbamazepine may be readily predicted by ab initio calculation, but we have found that the prediction of vibrational spectroscopic properties is rather dependent on the computational method used, particularly in systems were there exists extensive -electron conjugation, as is the case in carbamazepine.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding pattern of the structure A, obtained in the DFT calculations, reminds of the one predicted using the MP2 method. The energy difference between the folded and open structures calculated from the MP2 method with polarization and diffuse functions (6-31+G * * ) is 41.05 kJ mol −1 [28]. The corresponding energy differences for the DFT method utilizing the localized orbitals and PW approach are 69.69 and 48.09 kJ mol −1 , respectively.…”
Section: Static Dft Calculationsmentioning
confidence: 99%
“…We performed static DFT calculations to obtain global and local minima of the ranitidine molecule, which were used as the starting configurations for the analysis of the molecular [28]. Since the RNT molecule is very flexible and has many degrees of freedom (see Fig.…”
Section: Static Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation